Evolution of microstructure and performance of n-type BiTeSe thermoelectric materials fabricated by multi-path equal channel angular extrusion. (September 2020) - Hu, Xiaoming; Fan, Xi' an; Feng, Bo; Kong, Dong; Liu, Peihai; Xu, Chenhui; Kuang, Zhixiang; Li, Guangqiang; Li, Yawei
Abstract: Poor repeatable thermoelectric properties and inevitable contamination are introduced in n-type polycrystalline Bi2 Te3 based alloys prepared by conventional powder metallurgy technology. In the present work, equal channel angular extrusion (ECAE) method was used to extrude the cast ingot directly via various routes (A, BA, BC, C) to obtain the BiTeSe polycrystalline bulk alloys with uniform microstructure and free contamination. All extruded bulks boasted the much stronger mechanical properties due to the grain refinement, and the much higher thermoelectric properties due to the simultaneous improvement of electrical and thermal transport performances, compared with that (22.06 HV0.05 and 0.009) of the initial cast ingot. Among all extruded bulks, the one extruded via route BC achieved the maximum Vickers hardness of 59.8 HV0.05 due to the most preferable grain refinement, and that via route A achieved the maximum dimensionless figure of merit ( ZT ) of 0.724 due to the strongly developed texture.